ESTIMATION OF MULTI-MODAL ANALGESIA ADEQUACY IN THE PERIOPERATIVE PERIOD AT LONG-TERMED TRAUMATIZING ABDOMINAL OPERATIVE INTERVENTIONS - V. Kh. Sharipova (Неотложная медицинская помощь, 2016)
PURPOSE OF THE STUDY. Improvement of perioperative multimodal analgesia at longtermed traumatizing abdominal interventions with estimation of its effectiveness.MATERIALS AND METHODS. Eighty six patients have been examined and divided into 3 groups depending on anesthesia and postoperative pain relief methods.RESULTS. The effectiveness of perioperative multimodal analgesia using methods affecting the whole pathogenesis of pain has been revealed. Minimal stress of central and peripheral hemodynamics parameters, less evident pain syndrome in the postoperative period, economic effect shown up by the decrease of the use of narcotic analgesics both in intra and postoperative period have been observed.CONCLUSION. Algorithm of perioperative multimodal analgesia at longtermed and traumatizing abdominal operative interventions has been developed.